Occurrence and lateralizing value of "rare" peri-ictal vegetative symptoms in temporal lobe epilepsy - Musilová, Klára; Kuba, Robert; Brázdil, Milan; Tyrlíková, Ivana; Rektor, Ivan (Epilepsy & behavior, 2010)
We retrospectively investigated rare peri-ictal vegetative symptoms (PIVS) in 380 seizures of 97 patients with temporal lobe epilepsy (TLE): 234 seizures of 60 patients with TLE with mesiotemporal sclerosis (TLE/MTS) and 146 seizures of 37 patients with TLE with other lesions (TLE/non-MTS) who were at least 2 years after epilepsy surgery and classified as Engel I. We assessed the following PIVS: peri-ictal cough (pC), peri-ictal water drinking (pWD), peri-ictal vomiting (pV), and peri-ictal spitting (pS). We observed pC in 24.7% of patients and 10% of seizures; pWD in 14.4% of patients and 5.9% of seizures; pV and pS occurred more rarely. Both pWD and pC occurred significantly more often in those with TLE of the non- language-dominant hemisphere. The limited occurrence of pV and pS made it impossible to perform statistical analysis for these symptoms. In patients with TLE, pC and pWD were quite frequent; we observed pV and pS less frequently. Both pC and pWD have a significant lateralizing value in TLE.
Keywords: dospělí; retrospektivní studie; Epilepsy, Temporal Lobe; Humans; lidé středního věku; Middle Aged; Young Adult; Functional Laterality; epilepsie temporálního laloku; kašel; automatismus; mladý dospělý; zvracení; pití; Vomiting; mužské pohlaví; funkční lateralita; Drinking; Adult; Longitudinal Studies; Adolescent; Cough; záchvaty; Seizures; ženské pohlaví; lidé; mladiství; Automatism; Male; longitudinální studie; Retrospective Studies; Female